An imaginative approach to teaching - Egan, Kieran (San Francisco, CA : Jossey-Bass, 2005)
A child's journey through school begins when they are not yet literate and ends when they are capable of complex, abstract thinking. This book shows how we can transform the experience of schooling in K - 12 classrooms and help students become knowledgeable and creative in their thinking.
Includes bibliographical references and index.
Keywords: Teaching; Creative thinking -- Study and teaching; Imagination in children